PROBLEMS OF HALAL CERTIFICATION FOR MSMES IN PEKIRINGAN VILLAGE - Grace Putri Hastino; Sherin Audia Maharani; Vina Maylani; Sania Faridha Farasanti; Moh. Sigit Gunawan (Ann Publisher, 2024)
Pekiringan Village, which was recorded in March 2024 to 300 MSMEs with various kinds of MSME products, after observation of the MSME actors, considered that there was no need for a halal certificate for each product produced because it was enough to believe in the use of halal raw materials, this deviated from the provisions of article 2 paragraph (1) of Government Regulation Number 39 of 2021 concerning the Implementation of the Halal Product Assurance Sector. The purpose of the research is to study and analyze various problems arising from MSME actors regarding the implementation of halal certification in Pekiringan Village and to approach MSME actors to understand the importance of halal certification for MSME actors. The results of this study are the Problems of MSME Actors Regarding Education on the Implementation of Halal Certification in Pekiringan Village, namely the lack of information and education for MSME actors, the fear of charging fees beyond the limits of reasonableness and accessibility when registering online makes it difficult for MSME actors in Pekiringan Village to register for halal certificates. Regarding the Regulation on Halal Certification Obligations for MSME Actors contained in Government Regulation Number 39 of 2021 concerning the Implementation of the Halal Product Assurance Field, this is a way for the Government to actively guarantee halal products evenly by researchers with the Community Empowerment Institute (LPM) of Swadaya Gunung Jati University to carry out community service by assisting the process of making Halal Certification for MSMEs in Pekiringan Village through the Program Halal certification is free. The contribution is making halal certificates, which the Community Empowerment Institute of the Independent University of Gunung Jati assists.